Efeito da sedação ou do piso na avaliação objetiva de claudicação em equinos com um sistema de sensores inerciais sem fio - Azevedo, Marcos da Silva (2015)
Examination during movement is a fundamental and complex stage of the clinical exam of horses. The physical exam can be influenced by some factors such as the horses’ temperament and ground surface on which the horse is examined. In the first study, we investigated the potential influence of using acepromazine or xylazine over the movement of horses with different temperaments using a system of objective assessment of lameness. In the second study, using the same objective methods of evaluation, we investigated the possible influence of the surface on which the horses were trotted. The results of the first study showed that the number of healthy and lame horses on the forelimbs, before and after use of acepromazine remained the same (seven healthy and nine lame); on the hindlimbs before treatment, five were healthy and eleven lame, after treatment eight were healthy and eight remained lame. The number of healthy and lame horses on the forelimbs before treatment with xylazine had eight horses of each condition; seven were lame after treatment and nine were healthy. Four horses were healthy and twelve limping of hindlimbs before treatment with xylazine; after treatment, nine were lame and seven remained healthy. There was no difference in maximum and minimum height of the head and pelvis, both on forelimbs or hindlimbs. In the second study, we investigated the influence of the type of surface where the animal is examined on the results obtained on the objective evaluation with wireless inertial sensors. The result of this study showed no difference in maximum or minimum height of the head, pelvis and vector sum in horses examined on concrete, sand or grass. Difference was observed on the number of strides made on sand compared to grass and concrete (p <0.0001) on fore and hindlimbs. Impact lameness on forelimbs was presented on a larger number of animals on the concrete surface, whereas elevation lameness was more prevalent on the grass surface. On the hin limbs more impact lameness was present on the grass surface, while the elevation lameness was observed in a greater number of animals on the concrete surface. In the first study the use of acepromazine or xylazine did not interfere with the lameness intensity measured by wireless inertial sensors in horses with different temperaments. The results of the second study demonstrated that the examination in motion can be performed on any of the tested surfaces without having to stick to a predetermined sequence, as there was no difference on the variables at the objective evaluation by wireless inertial sensors.